Relationships Between Transcranial Doppler Velocity, Von Willebrand Factor, Factor VIII, and Hematological Parameters in Children with Sickle Cell Anemia: A Comparative Cross-Sectional Study. (October 2022) - Enifeni, Eniola Kehinde; Ogbenna, Ann Abiola; Daramola, Alaba Olanrewaju; Adewoyin, Ademola Samson; Olatunya, Oladele Simeon; Temiye, Edamisan
Background and Objectives: Sickle cell anemia (SCA) is associated with recurrent acute inflammatory processes. These inflammatory processes could lead to elevation of Factor VIII and Von Willebrand Factor levels, thereby increasing the risk of stroke in SCA children. This study aims to determine vWF/FVIII levels in children with SCA and their association with abnormal transcranial Doppler (TCD). Subjects and Methods: This study enrolled 75 children, including 24 SCA cases with normal TCD, 27 SCA cases with abnormal TCD, and 24 Hb AA controls, all aged between 2 and 16 years. Transcranial Doppler (TCD) ultrasound was performed to measure the cerebral blood velocity. Venous blood drawn from each participant was used to determine the levels of von Willebrand Factor Antigen (vWF: Ag) and Factor VIII (FVIII) and the complete blood count (CBC). Relationships among the measured parameters were determined using SPSS version 25. Statistical significance was set at P < .05. Results: FVIII and vWF levels were significantly higher among children with SCA compared to the Hb AA controls ( P < .001). Although SCA patients with abnormal TCD tended to have higher levels of FVIII and vWF, this result did not attain statistical significance ( P > .05). There was a moderate negative correlation between the left middle cerebral artery and FVIII, (r = −0.332; P = .017). Children with SCA showing an abnormal TCD velocity had significantly higher platelet count compared to those with normal TCD ( P = .018). Conclusion: Children with SCA have elevated levels of FVIII and vWF, and an abnormal TCD velocity is associated with elevated platelet count.